A coastline is an immeasurable thing : a memoir across three continents - Daniel, Mary-Alice (Ecco, an imprint of HarperCollins Publishers, 2022)
"Mary-Alice Daniel's family moved from West Africa to England when she was a very young girl, leaving behind the vivid culture of her native land in the Nigerian savanna. They arrived to a blanched, cold world of prim suburbs and unfamiliar customs. So began her family's series of travels across three continents in search of places of belonging. A Coastline Is an Immeasurable Thing ventures through the physical and mythical landscapes of Daniel's upbringing. Against the backdrop of a migratory adolescence, she reckons with race, religious conflict, culture clash, and a multiplicity of possible identities. Daniel lays bare the lives and legends of her parents and past generations, unearthing the tribal mythologies that shaped her kin and her own way of being in the world. The impossible question of which tribe to claim as her own is one she has long struggled with: the Nigerian government recognizes her as Longuda, her father's tribe; according to matrilineal tradition, Daniel belongs to her mother's tribe, the nomadic Fulani; and the language she grew up speaking is that of the Hausa tribe. But her strongest emotional connection is to her adopted home: California, the final place she reveals to readers through its spellbinding history. Daniel's approach is deeply personal: in order to reclaim her legacies, she revisits her unsettled childhood and navigates the traditions of her ancestors. Her layered narratives invoke the contrasting spiritualities of her tribes: Islam, Christianity, and magic. A Coastline Is an Immeasurable Thing is a powerful cultural distillation of mythos and ethos, mapping the far-flung corners of the Black diaspora that Daniel inherits and inhabits. Through lyrical observation and deep introspection, she probes the bonds and boundaries of Blackness, from bygone colonial empires to her present home in America"--